A single-cell transcriptomic dataset of enterocyte-specific HHEX knockdown in the Drosophila larval midgut. - Tu, Z.; Hu, Q.; Jia, Z.; Wang, Y.; Yu, T.; Liu, L.; Xu, X.; Hu, Y.; Wang, M. (Scientific data, 2025)
The hematopoietically-expressed homeobox protein (HHEX), an evolutionarily conserved regulator of endodermal organogenesis, remains uncharacterized in intestinal epithelial differentiation. To address this gap, we developed a Drosophila enterocyte-specific HHEX knockdown strain (NP1-Gal4 > UAS-HHEX [RNAi]) and generated a comprehensive cellular atlas of Drosophila third-instar larval (L3) midgut by single-cell RNA sequencing to precisely dissect HHEX's regulation. Our analysis delineated major midgut lineages including adult midgut progenitors (AMPs), enteroendocrine cells (EEs), and functionally distinct enterocyte (EC) subtypes defined by metabolic genes. HHEX depletion significantly reduced EC abundance while preserving subtype diversity. This inaugural single-cell transcriptomic comparison delivers a precision transcriptional atlas of HHEX-deficient Drosophila midgut for studying HHEX's critical role in regulating midgut epithelial maturation, while providing a roadmap to explore potential HHEX-regulated endodermal patterning conservation in mammalian systems.